THE INFLUENCE OF VALUE PERCEPTIONS ON PURCHASE INTENTION TOWARDS LUXURY FASHION PRODUCTS IN JAKARTA - Made Candra; Fiter Abadi (Jurnal Bina Manajemen, 2018)
In general, luxury market is growing in several countries, including Indonesia. Growth luxury market in a country related with the luxury trends on a particular country. The trends of luxury products consumption are very high causing there so many luxury counterfeit products spreading over the world including Indonesia. It is important to analyze the influence of purchase intention towards luxury fashion products. Since the number of counterfeit luxury fashion products is very high, fashion luxury product companies should identify and analyze what exactly factors influence purchase intention towards original luxury fashion products based on customers value perception. This research analysed concerning some variables such as: Functional Value Perceptions, Personal Value Perceptions, and Social Value Perceptions want to identify the most significantly influencing purchase intention towards luxury fashion products. This research use SPSS 21 through Multiple Regression Analysis for data analysis from quantitative research of 100 respondents. The results shows that all hypotheses are accepted and the most significantly influencing purchase intentions towards luxury fashion products is Functional Value Perceptions with usability, quality, and uniqueness as its indicators. Keywords: Functional Value Perceptions, Personal Value Perceptions, Social Value Perceptions, Luxury Fashion Products, Purchase Intention.